2013
DOI: 10.4103/0019-509x.118721
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free DNA concentration and integrity as a screening tool for cancer

Abstract: The combined use of CFDNA concentration and integrity is a candidate for a universal screening test of cancer. Upon setting suitable boundaries for the test it might be applied to identify cancer patients, particularly among subjects with predisposing factors. Being less expensive, CFDNA concentration could be applied for mass screening and for patients with values overlapping those of normal and benign subjects, the use of the more expensive, yet more specific, integrity test is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
5
12
0
Order By: Relevance
“…However, there was no statistically significant difference in the level of CEA between COPD and control subjects. This is matched with Zaher et al [23] Stated that CFDNA represented a highly sensitive and specific marker to discriminate cancer patients from control and benign individuals when compared to conventional tumor markers used in various types of cancer diagnosis.…”
Section: Discussionsupporting
confidence: 71%
“…However, there was no statistically significant difference in the level of CEA between COPD and control subjects. This is matched with Zaher et al [23] Stated that CFDNA represented a highly sensitive and specific marker to discriminate cancer patients from control and benign individuals when compared to conventional tumor markers used in various types of cancer diagnosis.…”
Section: Discussionsupporting
confidence: 71%
“…Even though we observed a significant difference in the plasma concentration of ALU115 and ALU247 between benign and malignant thyroid nodules, its clinical utility is limited due to a significant overlap. Although various studies have reported an increase in DNA concentration in cancer patients (22)(23)(24)(25)(26), numerous studies have indicated the limited utility of cfDNA concentration as a biomarker, owing to the wide variations in cfDNA level among the population (11). Moreover, we observed that the concentration difference could be attributed to the size of the lesions since patients with benign lesions were characterized by the larger tumor size, which was associated with the higher ALU115 and ALU247 levels.…”
Section: Discussionmentioning
confidence: 64%
“…Although cfDNA levels were not associated with ER or PR, they were significantly higher in HER-2-positive patients than in HER-2-negative patients [ 15 , 28 ]. Most researchers [ 15 , 25 28 , 30 31 ] showed a higher level of cfDNA in node-positive patients compared to node-negative patients, and as more lymph nodes are involved, more cfDNA could be detected in circulation [ 28 ]. Also, two studies [ 15 , 30 ] reported significant differences in the level of cfDNA between node-positive patients and node-negative patients, which suggested that the concentration of cfDNA might be a possible marker of early lymph node metastasis in breast cancer.…”
Section: Resultsmentioning
confidence: 99%